2007
DOI: 10.1016/j.jcf.2006.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure in cystic fibrosis as an indicator of disease severity

Abstract: Our data analysis supports the argument that the percentage of predicted REE is an objective indicator of disease severity and progression as well as energy requirements in the assessment of CF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Benefits of moderate intensity exercise for patients with CF have been demonstrated, especially in relation to improved sputum expectoration [30]. On the other hand, an elevated rest energy expenditure, compared to normal levels, have been documented in individuals with CF [31] and chronic obstructive pulmonary disease [32], since it is associated with the severity of changes in pulmonary physiology [33]. The results presented in this review indicate that energy expenditure values are higher during video game activities in comparison to the tests or exercise used.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of moderate intensity exercise for patients with CF have been demonstrated, especially in relation to improved sputum expectoration [30]. On the other hand, an elevated rest energy expenditure, compared to normal levels, have been documented in individuals with CF [31] and chronic obstructive pulmonary disease [32], since it is associated with the severity of changes in pulmonary physiology [33]. The results presented in this review indicate that energy expenditure values are higher during video game activities in comparison to the tests or exercise used.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in resting metabolic rate in adults with cystic fibrosis not in exacerbation is on the order of 30% (body weight, 30 vs 23 kcal/kg in healthy adults 4 , 17 ). Moudiou et al 5 found such resting metabolic rate increases to be confined to patients with cystic fibrosis exhibiting pancreatic insufficiency, although it seems unlikely that the pancreatic insufficiency per se was the cause of the elevation. The patients with pancreatic insufficiency also had greater impairment of pulmonary function and a lower body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…This elevation is a reflection of the increasing difficulty that patients with cystic fibrosis have in removing carbon dioxide produced by metabolism. Exacerbating this difficulty, the patient with cystic fibrosis has an elevated rate of resting metabolism 4 7 and, therefore, a higher‐than‐usual load of carbon dioxide to remove. In the current study of critically ill patients with cystic fibrosis receiving mechanical assistance from a ventilator, peak airway pressure and end‐tidal CO 2 values were higher than those of a similar group of patients without cystic fibrosis, even though the amount of carbon dioxide that needed to be eliminated was the same between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect calorimetry is the most commonly used and noninvasive method for measuring REE in clinical populations, as well as in CF 13 , 14 . We found no studies that compared the validity of prediction equations for energy requirements pre‐LTx and post‐LTx with measured values.…”
mentioning
confidence: 90%